Radio at Home: BBC Drama and the Domestic Listener, 1935–1942. Issue 1 (March 2015) - Goody, Alex
<x xml:space="preserve">Abstract</x> In the years before, and at the outbreak of, the Second World War radio drama on the BBC emerged as a genre through which particular questions about nation, home, decency and morality were articulated. At the same time listener research developed, under the auspices of Reith's BBC, as a vehicle for understanding the preferences, habits and situations of the radio audience. Drama and Features were the first areas of radio output subject to targeted research. The reports that were produced by the BBC Listener Research Section provide an invaluable picture both of the nature and responses of specific communities of listener, and of how the radio listener her/himself was conceived. Such evidence can be usefully analysed alongside the types of drama that were developed and broadcast during this period. This essay examines the different kinds of listening subjects there were for radio drama in Britain in the 1930s and early 1940s, how they intersected with contemporary conceptions of the listener, and what situations (both private and political) came to be meaningful in the event of listening.